Interpreting Public Perceptions of Early Childhood Education Teacher Professionalism: A Phenomenological Study in Pamekasan Regency - Danang Prastyo; Selfi Lailiyatul Iftitah; Ardhana Reswari; Alfarobi ahmad sulaiman (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2026)
The professionalism of early childhood education teachers is an important issue because public perception of professionalism is determined not only by formal government standards, but also by social constructs formed through local cultural values. The gap between formal standards and public perception can hinder improvements in the quality of early childhood education, especially in areas with strong local wisdom such as Pamekasan Regency. This study aims to interpret public perceptions of the professionalism of early childhood education teachers in Pamekasan Regency to reveal how the community defines professionalism based on their experiences and local values, the socio-cultural factors that shape perceptions, and their influence on teachers' professional practices.The study used a qualitative phenomenological approach with in-depth interviews with 30 informants, participatory observation in five early childhood education institutions, and focus group discussions. The data were analyzed using Colaizzi's method to identify the meaning structure of the informants' experiences. The results showed that the Pamekasan community interpreted the professionalism of PAUD teachers through three dimensions: religious and moral competence as the main foundation, caring parenting skills, and mastery of pedagogical knowledge as a complement. A pesantren background and understanding of Islam were more highly valued than formal academic qualifications. The study concluded that the community's perception of PAUD teacher professionalism is shaped by local cultural values and Islamic traditions that are not always in line with formal standards. The research recommendation is that teacher professionalism improvement programs need to consider local values and involve community leaders to create a contextual professional development model.